Oral and Dental Laser Treatments for Children: Applications, Advantages and Considerations - Ramazani, Nahid; Ahmadi, Rahil; Daryaeian, Mohammad (Journal of Lasers in Medical Sciences, 2012)
It is of utmost importance to make children interested in and willing to use dental services in order to prevent and treat oral diseases. Therefore, pediatric dental practitioners need to learn new technologies such as lasers, in addition to basic principles. Lasers have opened new horizons in the treatment of both soft and hard oral tissue problems in children. The present article describes application of the most commonly used lasers and their advantages and considerations.